Field Sampling : Principles and Practices in Environmental Analysis. - Conklin, Alfred R., Jr. (Alfred Russel), 1941- (Books in soils, plants, and the environment., 2004)
This reference describes in detail all the essential elements for the development and execution of a successful sampling plan at both contaminated and uncontaminated sites, leading the reader through presampling, planning, specific sampling situations and correct sample labelling, shipping, storage and examination.